2013
DOI: 10.2174/0929867311320140007
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Nanoparticles for Melanoma Cancer Treatment by Photodynamic Therapy and Electrochemotherapy Using Aminolevulinic Acid Derivatives

Abstract: For some time Photodynamic Therapy and electrochemotherapy have been used as alternative therapies against skin cancer. The primary aim of this work was to develop, characterize, and evaluate the in vitro cytotoxic activity of new drug delivery systems based on chitosan nanoparticles containing aminolevulinic acid derivatives such as prodrug (5-ALA and its ester derivative 8-ALA). The second goal of this study was to evaluate the synergistic effect of a combination of classical Photodynamic Therapy and electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…[11][12][13] Both of these polymers are widely reported for development of various drug delivery systems, in particular chitosan nanoparticles for melanoma treatment. 14,15 Natural compounds with antitumor properties are of great interest, since they are rather cheap and non-toxic for normal cells. Thymoquinone which was selected here as a model lipophilic drug, is a main active component of black seed essential oil.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Both of these polymers are widely reported for development of various drug delivery systems, in particular chitosan nanoparticles for melanoma treatment. 14,15 Natural compounds with antitumor properties are of great interest, since they are rather cheap and non-toxic for normal cells. Thymoquinone which was selected here as a model lipophilic drug, is a main active component of black seed essential oil.…”
Section: Introductionmentioning
confidence: 99%
“…The photosensitizer excited by ALA could contribute to the generation of reactive oxygen species, which induces oxidative damage and consequently leads to cell death [35]. Ferreira et al indicated that melanoma cancer could be treated by photodynamic therapy using ALA [36]. Prior studies observed that 5-ALA was a promising candidate for CRC diagnosis, and 5-ALA mediated photodynamic therapy could be a therapeutic strategy for CRC [37,38], which is consistent with our nding that ALA is an effective drug for CRC treatment.…”
Section: Establishment Of the Read Stage Prognostic Modelmentioning
confidence: 99%
“…Moreover, the use of multimodal therapies leading to synergistic effect has become a promising approach to enhance anti-cancer therapy, reduce undesirable systemic toxicity and side effects (123). PDT along with magnetohyperthermia, photothermal therapy and electrochemotherapy using nanomaterials has also been studied with the perspective of achieving enhanced therapeutic cancer treatments (123130). Magnetohyperthermia refers to a temperature rise caused by energy dissipation in the form of heat from magnetic nanoparticles that respond to an alternated frequency magnetic field.…”
Section: Perspectives On the Application Of Nanotechnology And Pdt Fomentioning
confidence: 99%